Downstream changes in spring-fed stream invertebrate communities: the effect of increased temperature range? - Russell G. DEATH; José BARQUN (Journal of Limnology, 2011)
Reduced thermal amplitude has been highlighted as a limiting factor for aquatic invertebrate diversity in springs. Moving downstream water temperature range increases and invertebrate richness is expected to change accordingly. In the present study temperature patterns were investigated in seven spring-fed streams, between April 2001 and November 2002, and compared to five run-off-fed streams to assess the degree of crenic temperature constancy. Temperature and physico-chemical characteristics of the water, and food resource levels were measured, and the invertebrate fauna collected at 4 distances (0, 100, 500 m and 1 km) from seven springs in the North and South Islands of New Zealand. Temperature variability was greater for run-off-fed streams than for springs, and increased in the spring-fed streams with distance from the source. Periphyton and physico-chemical characteristics of the water did not change markedly over the 1 km studied, with the exception of water velocity and organic matter biomass, which increased and decreased, respectively. The rate of increase in temperature amplitude differed greatly for the studied springs, probably being affected by flow, altitude, and the number and type of tributaries (i.e., spring- or run-off-fed) joining the spring-fed stream channel. Longitudinal changes in the number and evenness of invertebrate taxa were positively correlated to thermal amplitude (rs = 0.8). Moving downstream, invertebrate communities progressively incorporated taxa with higher mobility and taxa more common in nearby run-off-fed streams. Chironomids and non-insect taxa were denser at the sources. Chironomid larvae also numerically dominated communities 100 and 500 m downstream from the sources, together with Pycnocentria spp. and Zelolessica spp., while taxa such as Hydora sp. and Hydraenidae beetles, the mayflies Deleatidium spp. and Coloburiscus humeralis, and the Trichoptera Pycnocentrodes spp., all had greater abundances 1 km from the sources. In conclusion, water temperature range was highly correlated with number of taxa, although other factors, such as substratum composition, stability and invertebrate drift, may also play an important role in the determination of longitudinal changes in invertebrate community composition and structure along spring-fed streams.